Additive Manufacturing of Polymer Composites - Blacklock, Matthew (MDPI - Multidisciplinary Digital Publishing Institute, 2024)
Three-dimensionally printed composites offer the opportunity for the rapid manufacture of complex components with bespoke material architectures that can be designed to prioritise performance in specific regions whilst focusing on weight savings elsewhere. Recent research in this field has demonstrated tremendous progress in overcoming some of the technical challenges associated with creating continuous fibre composites using additive manufacturing, and new-to-market commercial printers offer the promise of broader adoption of these materials. Some of the remaining key challenges limiting widespread use are an understanding of the key mechanisms of failure and how these materials perform over the long term in a wide range of environments. This Special Issue features articles showcasing the latest research in the additive manufacture of polymer composites.